Kebenaran Pancasila sebagai Dasar Negara dalam Pandangan Mahasiswa Program Studi Pendidikan Pancasila dan Kewarganegaraan - Sumaryati, Sumaryati; Sukmayadi, Trisna (Universitas Negeri Malang, 2021)
This study aimed to describe the Pancasila and Citizenship Education study students' knowledge about the position of Pancasila as the state's basis and the true theory, students' views regarding the truth of Pancasila as the basis of the state, and efforts to improve the quality of the truth of Pancasila as the state's basis from the perspective of students. This study used a qualitative approach with a descriptive type of research. The technique of collecting data was through interviews conducted in discussions. Data analysis used data reduction techniques, data classification, data triangulation, data confirmation, and conclusions. The study results showed that students knew Pancasila as the basis of the state and the theory of truth of coherence, correspondence, pragmatism, and performative. Students' views on the five values of Pancasila were not implemented by Indonesian society and have not been fully beneficial in all areas of state and social life. Efforts to improve the quality of the truth of Pancasila as the state's basis could be made by increasing understanding of the five precepts of Pancasila, improving the curriculum, approaching all scientific fields, and forming a community of civilizing Pancasila values.